THE ROLE OF ACCOUNTING IN TAX POLICY: ITS IMPACT ON ECONOMIC DEVELOPMENT (Modern education and development, 2025)
This article is devoted to the study of the topic "the role of accounting in tax policy: its impact on economic development." The article analyzes the relationship between accounting and tax policy, as well as the importance of accounting information in the fulfillment of tax obligations. Accounting plays an important role in determining the financial condition of organizations and calculating tax payments, which contributes to economic stability and development. The article also reflects on the impact of tax policies on the economic growth and investment environment, methods for assessing the effectiveness of tax regimes through accounting, and how organizations develop tax strategies. International experiments and practices are also considered in order to further deepen the correlation.